Efficacies of Vancomycin, Arbekacin, and Gentamicin Alone or in Combination against Methicillin-Resistant Staphylococcus aureus in an In Vitro Infective Endocarditis Model - Lee, Dong-Gun (American Society for Microbiology, 2003)
We adopted an in vitro infective endocarditis model (IVIEM) to compare the efficacy of vancomycin (VAN), arbekacin (ABK), and gentamicin (GEN) alone or in combination. Using two strains of clinically isolated methicillin-resistant Staphylococcus aureus, one GEN susceptible (GS171) and one GEN resistant (GR153), fibrin clots were prepared and suspended in the IVIEM. Antibiotics were given as boluses every 6 h (q6h), q12h, or q24h or by continuous infusion with VAN, q12h or q24h with ABK, and q8h or q24h with GEN. For combination treatment, VAN q12h plus ABK q24h and VAN q12h plus GEN q24h were given. Fibrin clots were removed from each model at 0, 8, 24, 32, 48, and 72 h, and the bacterial densities were determined. The number of colonies within the fibrin clot was significantly decreased in all study groups compared with control groups (P < 0.001). When VAN and ABK were administered alone, the number of colonies was significantly lower in GS171 than in GR153 by 8 h after administration (P = 0.02) and was lowest in GS171 when ABK was administered q12h (P = 0.01). At 72 h, ABK or VAN alone produced equivalent bacterial reductions regardless of dosing frequency and GEN resistance. In GR153, VAN plus ABK showed an additive effect till 24 h, although VAN plus GEN showed indifference. Our data suggest that ABK could be used as an alternative to VAN in GEN-resistant staphylococcal endocarditis. An additive effect was seen when VAN and ABK were used together in GEN-resistant strains until 24 h; however, further studies are warranted for the clinical application of this combination.